The third wheel - Kinney, Jeff (Kinney, Jeff. Diary of a wimpy kid, 2014)
Love is in the air, but what does that mean for Greg Heffley? A Valentine's Day dance at Greg's school has turned his world upside down. As Greg scrambles to find a date, he's worried he'll be left out in the cold on the big night. His bestfriend, Rowley, doesn't have any prospects either but that's small consolation. Then an unexpected twist gives Greg a partner for the dance and leaves Rowley the odd man out. But a lot can happen in one night, and in the end, you never know who's going to be lucky in love . . .